Análisis Financiero y evaluación al Capital de Trabajo en la Ferretería “Ferroamerica” de la Ciudad de Loja Periodo 2014 - 2015 - Paladines Reyes, Leticia Del Carmen (2017)
The thesis work entitled FINANCIAL ANALYSIS AND EVALUATION TO THE CAPITAL OF WORK IN THE "FERROAMERICA" FERRETERÍA OF THE CITY OF SHOP PERIOD 2014 - 2015. It had as general objetive: to carry out a financial analysis and evaluation to the working capital of the hardware store "FERROAMERICA" Period 2014-2015, in order to present a solution to the economic and financial problems that this company is going through, it was proposed the specific objectives, which were oriented to the operational capacity of the hardware in the generation of utility and stability Financial. In order to comply with the first proposed objective, the vertical and horizontal analyzes were carried out to the financial statements, obtaining their corresponding relative values as percentages of each group and account more significant in such a way that the economic and financial structure was fully known and determined The variations that the accounts suffer from one period to another. Similarly, financial indicators were used to assess the degree of liquidity, activity, indebtedness and profitability, obtaining variation in the two years analyzed 2014-2015, which are shown and reflected with their respective interpretation in each financial ratio. The working capital of the hardware store was then evaluated to determine the shortcomings in the management and destination of current assets and liabilities, thus improving the successes and strengths that could affect the normal development of its economic activity. Finally, in order to comply with the last objective estimated for the present investigation, and as a result of the analysis and evaluation of the working capital made at the "FERROAMERICA" hardware store, the financial report was prepared, disclosing the economic and financial position in which Is the company since it contains recommendations of the most important points that at the discretion of the author benefit both in administrative and financial work, which will have a greater impact on users, due to the quality of the service offered. In conclusion at the end of the thesis it was determined that within the results obtained from the financial analysis regarding its liquidity, we have that the hardware store does not have enough available to cover its liabilities in the short term, affecting the credibility of it, It also has a high level of short-term debt, which affects the results of the periods analyzed and in terms of their level of profitability it can be seen that the gross profit margin is low, since the hardware fixes prices with a Minimum margin between cost and selling price. It is recommended to improve the liquidity of the hardware store through the increase of capital for the operation of the cash conversion cycle, it is also necessary to establish a strategy for a greater turnover of inventories; In terms of profitability, it is recommended to negotiate with suppliers in order to obtain purchase prices for products at lower prices than the current ones. In order to have economic and financial decisions, it is recommended that the corresponding indicators be prepared in advance.